Oli and Gas Explorations via Satellite Remote Sensing Techniques for AL_Nasiriya - Behadili, Suhad Faisal; Sayed, Baqir H. (Iraqi Journal of Science, 2019)
This study investigates data set as satellite images of type multispectral Landsat-7, which are observed for AL_Nasiriya city, it is located in southern of Iraq, and situated along the banks of the Euphrates River. These raw data are thermal bands of satellite images, they are taken as thermal images. These images are processed and examined using ENVI 5.3 program. Consequently, the emitted Hydrocarbon is extracted, and the black body algorithm is employed. As well as, the raster calculations are performed using ArcGIS, where gas and oil features are sorted. The results are estimate and determine the oil and gas fields in the city. This study uncovers, and estimates several unexplored oil and gas fields. Whereas, the real oil and gas exploration is high costly regarding to actual existed ones in proportional to human and equipment. For future, it is intended to perform domain oil and gas exploration in order to compare between the presented results of this study with the actual existed ones.